2023
DOI: 10.1021/acs.analchem.2c04604
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of a Broad Range of Carbonyl Metabolites in Exhaled Breath by UHPLC-MS

Abstract: Analysis of volatile organic compounds (VOCs) in exhaled breath (EB) has shown great potential for disease detection including lung cancer, infectious respiratory diseases, and chronic obstructive pulmonary disease. Although many breath sample collection and analytical methods have been developed for breath analysis, analysis of metabolic VOCs in exhaled breath is still a challenge for clinical application. Many carbonyl compounds in exhaled breath are related to the metabolic processes of diseases. This work … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 47 publications
0
7
0
Order By: Relevance
“…In clinic, only one metabolite detection is normally unreliable and normally requires joint detection of multiple metabolites. , Moreover, in some cases, more than one kind of aldehydes may exist in the disease. ,, Thus, we further explored the possibility of this light-assisted strategy for several aldehyde metabolites coexisting in one sample simultaneous identification. Without loss of generality, Val, Hep, 2-Fur, 10-Und, and Ben in ammonium acetate buffer were mixed with the Se nanoprobe followed by light-assisted AIMS detection.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In clinic, only one metabolite detection is normally unreliable and normally requires joint detection of multiple metabolites. , Moreover, in some cases, more than one kind of aldehydes may exist in the disease. ,, Thus, we further explored the possibility of this light-assisted strategy for several aldehyde metabolites coexisting in one sample simultaneous identification. Without loss of generality, Val, Hep, 2-Fur, 10-Und, and Ben in ammonium acetate buffer were mixed with the Se nanoprobe followed by light-assisted AIMS detection.…”
Section: Resultsmentioning
confidence: 99%
“…22,23 Moreover, it has been reported that aldehydes with very small molecular (less than six carbon atoms) or large molecular (more than 10 carbon atoms) weights are difficult to be detected. 6,24,25 Chemical isotope labeling (CIL) has demonstrated great success in mass spectrometry (MS) with enhanced sensitivity and accuracy. 26,27 In addition, selenium compared with other elements is easily recognized because of its characteristic isotope peak distribution in the MS spectrum.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A quaternary ammonium compound, 2-(aminooxy)ethyl- N,N,N -trimethylammonium (ATM) triflate, was used to coat the surfaces of the micropillars as previously described. 9 , 17 , 18 ATM adsorbs to the silicon dioxide surfaces of the micropillars via electrostatic and hydrogen bond interactions. ATM chemoselectively traps carbonyl compounds in exhaled breath by means of oximation reactions.…”
Section: Methodsmentioning
confidence: 99%
“…The procedure for the capture of carbonyl compounds in air and exhaled breath has been described previously. 9 , 17 , 18 To summarize, the exhaled breath collected in 1-L Tedlar bags was drawn through the microreactor chip by applying a vacuum at a flow rate of 7 mL/min. After this process, ATM adducts in the microreactors were eluted with 200 μL of water from a slightly pressurized small vial.…”
Section: Methodsmentioning
confidence: 99%